2006
DOI: 10.1590/s0102-695x2006000200020
|View full text |Cite
|
Sign up to set email alerts
|

Berinjela (Solanum melongena L.): mito ou realidade no combate as dislipidemias?

Abstract: RESUMO:A dislipidemia é considerada um dos fatores de risco mais importantes para o desenvolvimento da doença arterial coronariana. Como resultado, tratamentos efetivos com fármacos foram desenvolvidos para combatê-la, porém, apresentam alto custo e efeitos colaterais. Considerando este fato, pacientes têm recorrido a tratamentos utilizando alimentos conhecidos científi ca e popularmente por possuírem efeito hipolipemiante. Várias pesquisas vêm sendo realizadas com esses alimentos como a berinjela no sentido d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 14 publications
0
9
0
3
Order By: Relevance
“…6 In addition, the eggplant peel is rich in anthocyanins and has therapeutic potential for the treatment of hyperlipidemia and prevention of atherogenic cardiovascular diseases by inhibiting lipid peroxidation. 7 Gonçalves et al 8 conducted a literature review comprising 25 articles on the species S. melongena and concluded that this species has a mitigation effect on dyslipidemia, particularly hypercholesterolemia, when used in the form of juice made from the fruit with peel.…”
Section: Introductionmentioning
confidence: 99%
“…6 In addition, the eggplant peel is rich in anthocyanins and has therapeutic potential for the treatment of hyperlipidemia and prevention of atherogenic cardiovascular diseases by inhibiting lipid peroxidation. 7 Gonçalves et al 8 conducted a literature review comprising 25 articles on the species S. melongena and concluded that this species has a mitigation effect on dyslipidemia, particularly hypercholesterolemia, when used in the form of juice made from the fruit with peel.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, consumption of eggplant (Solanum melongena L.) has increased considerably due to its medicinal properties (GONÇALVES et al, 2006;RAIGÓN et al, 2008), mainly because of its cholesterol-reducing properties (JORGE et al, 1998) and hypoglycemic effect (DERIVI et al, 2002). Eggplants are rich in vitamins B1 and B2 and minerals including calcium, phosphorus, iron, and potassium (RIBEIRO et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Por conter em sua composição substâncias com supostas ações terapêuticas, a berinjela (Solanum melongena L.) tem sido citada por diversos autores como um dos vegetais que podem ser classificados como alimento funcional. Estudos relatam o seu uso no controle de altos níveis plasmáticos de colesterol e nas dietas para emagrecimento, tornando-se assim importante na dislipidemia e obesidade [8][9][10] .…”
Section: Introductionunclassified